Developing a multi-touch serious game to fight the digital divide : the Portuguese ATM a pilot case study - Carvalho, Diana (2012)
The use of Information and Communication Technologies (ICTs) has grown substantially over the past few years. However, a portion of the world’s society has not been able to keep up with these technological advances. For this purpose, we present a serious game with a multi-touch interface envisioned to encourage and teach digitally excluded people on how to use the Portuguese Automated Teller Machine (ATM): a commodity much needed by society, but still avoided by some, mainly due to their fear of the digital world. An exploratory study was conducted to investigate if a serious game based on a new interaction paradigm can have a positive influence in the struggle against the Portuguese digital divide. We believe that the findings of our pilot case study can be useful to determine if a multi-touch serious game, due to its intuitiveness and ease of use, can stimulate the digitally excluded people to handle the ATM on a regular basis. The results that were obtained suggest that this approach may indeed produce a positive impact in the attempt to bridge the Portuguese digital divide.